2007
DOI: 10.1002/ijc.23059
|View full text |Cite
|
Sign up to set email alerts
|

Association between lung cancer risk and single nucleotide polymorphisms in the first intron and codon 178 of the DNA repair gene, O6‐alkylguanine–DNA alkyltransferase

Abstract: The association between lung cancer risk and 2 polymorphisms, rs12268840 and rs2308327 (codon K178R), in the DNA repair protein, O 6 -alkylguanine-DNA alkyltransferase, which are associated with interindividual differences in activity, have been investigated in 3 hospital-based case-control studies. Genotyping was carried out on 617 subjects of whom 255 had lung cancer. In 2 of the 3 series, there was a significant inverse association between the 178R allele and case status (p < 0.05). In a meta-analysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(59 reference statements)
1
7
1
Order By: Relevance
“…Some of these SNPs have been reported to have an effect on MGMT activity (24). In addition, the c.427A>G and c.533A>G polymorphisms have been associated with increased cancer risk by some authors (25,26) whereas others did not detect this association (27,28). In our series, the c.427A>G and c.533A>G SNPs were found in 5% of the patients, i.e., were present at a lower frequency than expected from the reported allele frequency of 11% to 28% in Caucasians (25).…”
Section: Discussioncontrasting
confidence: 64%
“…Some of these SNPs have been reported to have an effect on MGMT activity (24). In addition, the c.427A>G and c.533A>G polymorphisms have been associated with increased cancer risk by some authors (25,26) whereas others did not detect this association (27,28). In our series, the c.427A>G and c.533A>G SNPs were found in 5% of the patients, i.e., were present at a lower frequency than expected from the reported allele frequency of 11% to 28% in Caucasians (25).…”
Section: Discussioncontrasting
confidence: 64%
“…However, six articles [26,27,28,29,30,31] irrelevant to MGMT Leu84Phe polymorphism and four articles [32,33,34,35] without detailed MGMT Leu84Phe genotypes data were excluded. In addition, three articles [10,36,37] were included by literature reading and manual searching.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies reported an association between intronic SNPs and disease risk [22-24]. Intronic SNPs could affect intronic splicing enhancer or silencer signals and thereby modulate the expression of different splice variants [25].…”
Section: Discussionmentioning
confidence: 99%